El peritaje contable como aporte científico en la solución de hechos controversiales en la fiscalía anticorrupción de la Región San Martín. Periodo 2012 - Silva Cayao, Yomar (2016)
The present research is referring to the accounting expertise as a scientific contribution in the solution of facts controversial in the cases presented in the Office of the prosecutor specializing in crimes of corruption of officials of the Region San Martin during the period 2012, where it is analyzed how it influences the performance of the expert accountant through his expert report being an element of proof necessary to determine the economic damage to the detriment of the Peruvian State, and the criteria with which is prepared to have the character of real evidence and credible. The inductive method was used, having come to establish that the work of the Expert Accounting is very important and crucial at the stage of the formalization of the preparatory research that contributes to clarify the points or facts controversial especially in economic matters of which the Prosecutor does not have the knowledge to be outside his specialty and function, as administrator of justice, allowing the Prosecutor get a test item objective that will allow to make his theory with justice and equality. That is why we came to the conclusion that the expert accountant must possess a solid training in the academic, scientific and professional experience, which allows to illustrate to the administration of justice on controversial facts through his report prepared under strict ethical standards, which will give a character of scientific test, with real and accurate results proven through documents, without arriving to subjective conclusions that are unfounded, and accelerating the judicial work. I hope that the present research and the results that have been reached, it serve as input for future research.